The Role of Nature Education in Developing Student Character in Building an Environmentally Caring Generation - Saputri, Dwi Yuniasih; Juliadilla, Risa (PT. Anagata Sembagi Education, 2024)
This study aims to explore the role of nature education in the development of students' character and its impact on environmental concerns. In the face of urgent environmental challenges, such as climate change and declining biodiversity, education is key to forming a generation that cares about the environment. To achieve this goal, the study uses the Systematic Literature Review (SLR) approach, which collects and analyzes a variety of relevant related studies. This method includes the identification, evaluation, and synthesis of previous research, so as to uncover emerging patterns and themes in the context of nature education. The results of the study showed that nature education significantly increased students' ecological awareness. Active involvement in outdoor activities—such as tree planting, beach cleanups, and conservation projects—encourages students to adopt eco-friendly behaviors. Through hands-on experience, students not only gain theoretical knowledge, but also build an empathetic and responsible attitude towards environmental sustainability. These findings emphasize the importance of integrating nature education in the curriculum, which not only shapes the character of students, but also prepares them to become responsible leaders in efforts to safeguard and preserve the environment. With this approach, it is hoped that future generations can be more active in overcoming global environmental challenges.